Keutamaan Menuntut Ilmu pada Puisi Faḍlut-ta’allum: Kajian Antologi Hidāyatul-ażkiyà ilā Ṭarīqil-auliyà Karya Syaikh Zainud-dīn al-Malībārī asy-Syāfi̒ī - Hidayatun Ulfa (Institut Islam Nahdlatul Ulama Temanggung, 2020)
This study discusses the primacy of the study found in the poems of Faḍlut-Ta’allum in the anthology of the Hidayatul-Ażkiyà ilā Ṭarīqil-Auliyà by Shaykh Zainud-Din al-Malībārī ash-Shāf̒.The analysis in this study refers to the study of semiotics proposed by Riffaterre. Based on the semiotic analysis carried out, it can be concluded that in the poem